2019
DOI: 10.2147/ijn.s214657
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Optimization Design Of Lactoferrin Loaded HupA Nanoemulsion For Targeted Drug Transport Via Intranasal Route</p>

Abstract: BackgroundHuperzine A (HupA) is a selective acetylcholinesterase inhibitor used to treat Alzheimer’s disease. The existing dosage of HupA lacks brain selectivity and can cause serious side effects in the gastrointestinal and peripheral cholinergic systems.PurposeThe aim of this study was to develop and characterize a HupA nanoemulsion (NE) and a targeted HupA-NE modified with lactoferrin (Lf) for intranasal administration.MethodsThe NE was formulated using pseudo-ternary phase diagrams and optimized with respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Huperzine A (HupA) is an alkaloid from some plants of genus Huperzia used as therapy for memory deficits and acetylcholine-deficit dementia such as AD [246] and to repair mitochondrial function by preserving membrane structural integrity and activity of ETC complexes as well as ATP synthesis in cellular and animal models of AD [247,248]. Nanosystems containing HupA have been described showing enhanced drug delivery compared to free drug or non-targeted NF in mouse brain after intranasal administration [249,250]. In addtion, PEG-PLGA NPs containing HupA show a higher memory recovery than free HupA in AD rats [251].…”
Section: Restoring Production and Utilization Of Mitochondrial Energy In Niandnddsmentioning
confidence: 99%
“…Huperzine A (HupA) is an alkaloid from some plants of genus Huperzia used as therapy for memory deficits and acetylcholine-deficit dementia such as AD [246] and to repair mitochondrial function by preserving membrane structural integrity and activity of ETC complexes as well as ATP synthesis in cellular and animal models of AD [247,248]. Nanosystems containing HupA have been described showing enhanced drug delivery compared to free drug or non-targeted NF in mouse brain after intranasal administration [249,250]. In addtion, PEG-PLGA NPs containing HupA show a higher memory recovery than free HupA in AD rats [251].…”
Section: Restoring Production and Utilization Of Mitochondrial Energy In Niandnddsmentioning
confidence: 99%
“…The intranasal administration of lactoferrin-HupA-NE in rats significantly ( p < 0.05) enhanced drug delivery to the brain compared to HupA-NE. The direct targeting index of lactoferrin-HupA-NE (3.21 ± 0.75) demonstrated brain targeting, and the area under the curve (AUC) 0–α for lactoferrin-HupA-NE was significantly higher ( p < 0.05) compared to HupA-NE [ 66 ].…”
Section: Intranasal Nes For Brain Disordersmentioning
confidence: 99%
“…Oil-in-water nano-emulsions are cloudy and surfactantstabilized heterogeneous drug delivery systems; they are composed of oil droplets (10-100 nm) dispersed in water or other aqueous solutions (Hort et al 2019;Karami et al 2019). On the other hand, nano-emulsions can be effectively used to encapsulate HupA with high protection against degradation and can be produced at the large scale (Jiang et al 2019). Jiang et al (2019) reported a new nano-emulsion-based system loaded with Lactoferrin for enhanced targeted drug delivery via intranasal administration.…”
Section: Nano-emulsion and Micro-emulsionsmentioning
confidence: 99%
“…On the other hand, nano-emulsions can be effectively used to encapsulate HupA with high protection against degradation and can be produced at the large scale (Jiang et al 2019). Jiang et al (2019) reported a new nano-emulsion-based system loaded with Lactoferrin for enhanced targeted drug delivery via intranasal administration. Their results showed the successful targeting of hCMEC/D3 cells, and their system is non-toxic and was highly stable up to 6 months (Jiang et al 2019).…”
Section: Nano-emulsion and Micro-emulsionsmentioning
confidence: 99%
See 1 more Smart Citation